2017
DOI: 10.1002/anie.201609288
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Probing of the UDP‐Apiose/UDP‐Xylose Synthase Reaction: Evidence of a Mechanism via a Coupled Oxidation and Aldol Cleavage

Abstract: The C‐branched sugar d‐apiose (Api) is essential for plant cell‐wall development. An enzyme‐catalyzed decarboxylation/pyranoside ring‐contraction reaction leads from UDP‐α‐d‐glucuronic acid (UDP‐GlcA) to the Api precursor UDP‐α‐d‐apiose (UDP‐Api). We examined the mechanism of UDP‐Api/UDP‐α‐d‐xylose synthase (UAXS) with site‐selectively 2H‐labeled and deoxygenated substrates. The analogue UDP‐2‐deoxy‐GlcA, which prevents C‐2/C‐3 aldol cleavage as the plausible initiating step of pyranoside‐to‐furanoside convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…For example, 2-fluoro-fucose inhibits the incorporation of fucose into Arabidopsis cell walls (Dumont et al, 2015;Villalobos et al, 2015). NDP-sugar interconversion has also been investigated using fluorinated compounds as described in studies using synthesized UDP-2-fluoro-glucuronic acid to monitor the conversion and mechanism of UDP-apiose formation by UDP-D-apiose/UDP-D-xylose synthase (Choi et al, 2011;Eixelberger et al, 2017). In maize and pea etiolated seedlings, 2-deoxyglucose inhibits callose production during gravitropic responses (Jaffe and Leopold, 1984).…”
Section: New Tools For Studying Cell-wall Recyclingmentioning
confidence: 99%
“…For example, 2-fluoro-fucose inhibits the incorporation of fucose into Arabidopsis cell walls (Dumont et al, 2015;Villalobos et al, 2015). NDP-sugar interconversion has also been investigated using fluorinated compounds as described in studies using synthesized UDP-2-fluoro-glucuronic acid to monitor the conversion and mechanism of UDP-apiose formation by UDP-D-apiose/UDP-D-xylose synthase (Choi et al, 2011;Eixelberger et al, 2017). In maize and pea etiolated seedlings, 2-deoxyglucose inhibits callose production during gravitropic responses (Jaffe and Leopold, 1984).…”
Section: New Tools For Studying Cell-wall Recyclingmentioning
confidence: 99%
“…It involves decarboxylation coupled to sugar ring contraction to generate a five-membered ring furanosyl product. [11][12][13] The enzyme also produces UDPxylose, a six-membered ring UDP-xylopyranose (3), in consistent ratios, typically about 1:1 at neutral pH. 6,13 A plausible reaction path has been proposed based on mechanistic studies spanning several decades, as shown in Figure 1.…”
mentioning
confidence: 99%
“…[11][12][13] The enzyme also produces UDPxylose, a six-membered ring UDP-xylopyranose (3), in consistent ratios, typically about 1:1 at neutral pH. 6,13 A plausible reaction path has been proposed based on mechanistic studies spanning several decades, as shown in Figure 1. 6,[9][10][11][12][13][14][15][16][17][18][19] The relative timing of the catalytic steps has been recently elucidated from kinetic isotope effects on the enzymatic rates as well as on the distribution of UDP-apiose (1a) and UDP-xylose (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations